2007
DOI: 10.1007/2288-6729-1-1-23
|View full text |Cite
|
Sign up to set email alerts
|

Early Childhood Education and Care in the United States: An Overview of the Current Policy Picture

Abstract: 1 Increased attention to early childhood education and care (ECEC) has been observed in all the industrialized countries but our focus here is on a current picture of ECEC in the United States (U.S.). Early childhood education and care (ECEC) in the U.S. includes a wide range of part-day, full-school-day, and full-workday programs, under educational, social welfare, and commercial auspices, funded and delivered

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
2
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 8 publications
0
38
2
3
Order By: Relevance
“…For instance, in 1965, only eighteen states had public kindergarten, and in 1970, less than 80% of five-year-old children attended public kindergarten. In 2000, all the states funded public kindergarten, and 98% of five-year-old children attended it (Kamerman and Gatenio-Gabel, 2007). The Head Start Program, which started in 1965 as a summer program with 561,000 children enrolled, was transformed the next year into a nine-month program, and in 2015, it served nearly one million children.…”
Section: The Evolution Of Preschool Educationmentioning
confidence: 99%
“…For instance, in 1965, only eighteen states had public kindergarten, and in 1970, less than 80% of five-year-old children attended public kindergarten. In 2000, all the states funded public kindergarten, and 98% of five-year-old children attended it (Kamerman and Gatenio-Gabel, 2007). The Head Start Program, which started in 1965 as a summer program with 561,000 children enrolled, was transformed the next year into a nine-month program, and in 2015, it served nearly one million children.…”
Section: The Evolution Of Preschool Educationmentioning
confidence: 99%
“…A recent cross-national study on the topic concluded that there were no clear negative consequences attached to the integration of ECCE services into the educational system (Kaga et al, 2010). Studies from countries with fragmented ECCE delivery systems show unequal access to services and wide-ranging quality, although several notable positive changes have been found as a result of recent efforts (Kamerman & Gatenio-Gabel, 2007;and Kaga et al, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, while many studies have analyzed ECCE financingspecifically on the level of public funding, financing schemes, and integration of the fragmented systemespecially in developed countries, this issue has been little discussed in Japan (Blau & Currie, 2006;Kamerman & Gatenio-Gabel, 2007;Bennet, 2008;Cleveland & Krashinsky, 2009;and Kaga et al, 2012). Although recent studies of ECCE in Japan have reviewed the general trends of its financing and the structure of the new system, analysis of the variation in the level and share of public funding by 1 Target 4.2 under SDG 4 is set to "by 2030, ensure that all girls and boys have access to quality early childhood development, care and pre-primary education so that they are ready for primary education" (UNESCO, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…According to several studies ([BAR07], [HAU97], [KAM07], [BAR95]], there are certain family attributes that play an important role in the development of young children including parental level of education, socio-economic status, parent-child interactions, and the family structure. Each of these factors can directly influence existing resources and home environment that either enhance or detract children's development [TRA93].…”
Section: Figure 2 Systemigram For the Pre-k Learning Environmentmentioning
confidence: 99%